FRI0048 The ANTI-CD20 antibody rituximab reduces the inflammatory and prothrombotic profile of leukocytes from rheumatoid arthritis patients and modulates the activity of endothelial cells. (15th June 2017) - Cecchi, I; Perez-Sanchez, C; Ruiz-Limon, P; Rosa, I Arias de la; Abalos-Aguilera, MC; Jimenez-Gomez, Y; Ortega, R; Collantes-Estevez, E; Escudero, A; Barbarroja, N; Sciascia, S; Lopez-Pedrera, C
Abstract : Background: Rituximab (RTX) has been shown to be successful in the treatment of rheumatoid arthritis (RA), indicating that B cells have an important role in this disease. Objectives: The present study was undertaken to investigate the mechanisms of action of RTX on the immune and endothelial cells (EC) of the vascular system in the setting of RA. Methods: Purified lymphocytes from five RA patients with high disease activity were treated with RTX (1ug/mL) for 24 hours. Then, the depletion of B cells was assessed by flow cytometry, and the changes occurred in the inflammatory profile of T-lymphocytes was analysed by RT-PCR. In a second set of experiments, to evaluate the influence of B-cell depletion on the inflammatory/prothrombotic profile of cells belonging to the vascular system, supernatants from cultured lymphocytes of RA patients in the presence or in the absence of RTX were added to isolated monocytes from AR patients and to cultured endothelial cells. The response to RTX was then examined. Results: As expected, RTX promoted a significant depletion of B-cells. In parallel, the inflammatory profile of T lymphocytes from RA patients was downregulated, as shown by a significant drop of IL-1, IL-6, IL-17, IFN and TNF expression levels, thus suggesting that the anti-inflammatory effects of RTX might be related to B cell depletion. Supernatants from RTX-treated lymphocytes further abridged the prothrombotic profile of RA-monocytes, promoting a significant inhibition of TF, MCP-1, IL-8, IL-1 and VEGF-A gene expression. Moreover, endothelial cells, activated after treatment with supernatants from cultured RA-lymphocytes, showed reduced expression of cell-adhesion molecules (i.e. V-CAM, I-CAM, E-Selectin) and pro-thrombotic factors (i.e. TF, VEGF, IL-8) after treatment with supernatants from cultured RA-lymphocytes in the presence of RTX. Conclusions: Overall, these results reveal that depletion of B-cells by RTX in RA influences the inflammatory profile of T lymphocytes, as well as their interaction with monocytes and ECs, thus modulating the inflammatory and prothrombotic shape of vascular cells in the setting of RA. Acknowledgements: Supported by CTS-794, ISCIII (PI15/01333; RIER RD16/0012/0015) Disclosure of Interest: None declared